KAJIAN MORFOLOGI PADA ASPEK MORFEM DALAM TEKS BERITA INFO TUBAN DI INSTAGRAM - A. Alfin Fatkhur Rohim; Sri Yanuarsih; I Wayan Letreng (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research focuses on the study of morphology in news texts published on the Info Tuban Instagram account. The purpose of this study is to describe the morphological processes contained in the news texts, including the use of morphemes, affixation, and reduplication. The research method used is descriptive qualitative with data collection techniques in the form of documentation of news posts from the Info Tuban account. The collected data were then analyzed based on morphological theory to identify word forms, structures, and formation processes. The results show that the Info Tuban news texts contain various morphological forms including prefixes, suffixes, confixes, and the use of word reduplication that serves to clarify meaning and provide emphasis on information. This study is expected to contribute to understanding the characteristics of language on social media and become a reference for linguistic research, especially in the field of morphology.